login
A216508
a(n) = 13*a(n-1) - 65*a(n-2) + 156*a(n-3) - 182*a(n-4) + 91*a(n-5) - 13*a(n-6), with initial terms 6, 13, 39, 130, 455, 1638.
7
6, 13, 39, 130, 455, 1638, 6006, 22308, 83655, 316030, 1200914, 4585308, 17577014, 67603887, 260757536, 1008258225, 3906958055, 15167837542, 58983478554, 229708325847, 895760071050, 3497141791455, 13667427167576, 53464307173927, 209315686335366, 820090746381088, 3215215287887889
OFFSET
0,1
COMMENTS
a(n) is equal to the rational part of 2*X(2*n) (with respect to the field Q(sqrt(13))), where X(n) = sqrt((13 + 3*sqrt(13))/2)*X(n-1) - sqrt(13)*X(n-2) + sqrt((13 - 3*sqrt(13))/2)*X(n-3), with X(0)=3, X(1)=sqrt((13 + 3*sqrt(13))/2), and X(2)=(13 - sqrt(13))/2.
The Berndt-type sequence number 3 for the argument 2Pi/13 defined by the relation a(n) + A216597(n)*sqrt(13) = 2*X(2*n), where X(n) := s(2)^n + s(5)^n + s(6)^n, where s(j) := 2*sin(2*Pi*j/13).
We note that all numbers of the form a(6*n+k)*13^(-n), where k = 1,...,6, n = 0,1,... are integers, and even the number a(13)*13^(-4) is an integer.
a(n) is also equal to the rational part of 2*Y(2*n) (with respect to the field Q(sqrt(13))), where Y(n) = sqrt((13 - 3*sqrt(13))/2)*Y(n-1) + sqrt(13)*Y(n-2) - sqrt((13 + 3*sqrt(13))/2)*Y(n-3), with Y(0)=3, Y(1)=sqrt((13 - 3*sqrt(13))/2), and Y(2)=(13 + sqrt(13))/2. Moreover we can deduce the following decompositions:
2*Y(2*n) = a(n) - A216597(n)*sqrt(13) and Y(n) = s(1)^n + s(3)^n + s(9)^n (we have s(9) = -s(4)) - Roman Witula, Sep 22 2012
REFERENCES
Roman Witula and D. Slota, Quasi-Fibonacci numbers of order 13, Thirteenth International Conference on Fibonacci Numbers and their Applications, Congressus Numerantium, 201 (2010), 89-107.
Roman Witula, On some applications of formulas for sums of the unimodular complex numbers, Wyd. Pracowni Komputerowej Jacka Skalmierskiego, Gliwice 2011 (in Polish).
LINKS
Roman Witula and D. Slota, Quasi-Fibonacci numbers of order 13, (abstract) see p. 15.
FORMULA
G.f.: -(91*x^5-364*x^4+468*x^3-260*x^2+65*x-6) / (13*x^6-91*x^5+182*x^4-156*x^3+65*x^2-13*x+1). - Colin Barker, Jun 01 2013
EXAMPLE
We have a(7)/2 + 2*A216597(7) = 26, 4*X(4) - X(6) = 13 + sqrt(13), 4*X(8) - X(10) = 91, 4*X(10) - X(12) = 13*(21 - sqrt(13)), 4*X(12) - X(14)= 78*(11 - sqrt(13)), 8*X(14) - 2*X(16) = 11*13*sqrt(13)*(3*sqrt(13) - 5) and X(6) - 10*X(2) = -6*sqrt(13) since 2*X(2) = 13 - sqrt(13), 2*X(4) = 39 - 5*sqrt(13), X(6) = 65 - 11*sqrt(13), 2*X(8) = 91*(5 - sqrt(13)), X(10) = 91*(9 - 2*sqrt(13)), X(12) = 3003 - 715*sqrt(13) = 13*(3*77 - 55*sqrt(13)), X(14) = 11154 - 2782*sqrt(13), 2*X(16) = 83655 - 21541*sqrt(13).
MATHEMATICA
LinearRecurrence[{13, -65, 156, -182, 91, -13}, {6, 13, 39, 130, 455, 1638}, 30]
CROSSREFS
KEYWORD
nonn,easy,changed
AUTHOR
Roman Witula, Sep 11 2012
EXTENSIONS
Better name from Joerg Arndt, Sep 17 2012
Name clarified by Robert C. Lyons, Feb 08 2025
STATUS
approved